2021
DOI: 10.7358/ecps-2021-023-ismi
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Students’ Intention to Use Mobile Learning at Universitas Negeri Semarang: An Alternative Learning from Home During Covid-19 Pandemic

Abstract: Coronavirus Disease (Covid-19) pandemic influenced education systems throughout the world, including in Indonesia. It makes the universities and schools go online for their teaching-learning process. Therefore, mobile learning can be an alternative solution to carry out the teaching and learning process as suggested by the government. The purpose of this study was to explore empirically mobile learning acceptances based on Technology Acceptance Model (TAM) with satisfaction as the mediating variable. The popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Less popular than LMS, pedagogically focused technologies such as online learning [87][88][89][90][91], mobile learning [15,44,73,[92][93][94][95], online education [81,84,96], online teaching [97][98][99][100], and emergency remote teaching [78,101,102] were investigated to a substantial degree. This illustrates an emerging trend to understand the acceptance of tools (such as LMS) rather than approaches.…”
Section: The Technologies Studiedmentioning
confidence: 99%
“…Less popular than LMS, pedagogically focused technologies such as online learning [87][88][89][90][91], mobile learning [15,44,73,[92][93][94][95], online education [81,84,96], online teaching [97][98][99][100], and emergency remote teaching [78,101,102] were investigated to a substantial degree. This illustrates an emerging trend to understand the acceptance of tools (such as LMS) rather than approaches.…”
Section: The Technologies Studiedmentioning
confidence: 99%
“…The obtained results in this paper fill a gap in the existing literature. In the field of economic education, there is interest in m-learning at the university level [3,42,44,121,122], but very little attention has been given to secondary education, particularly in the post-pandemic period after returning to classrooms. Previous cross-country study (Poland, Croatia, Serbia) [2], addresses the topic of economic education through e-learning at the high school level, and this present research can contribute to the development of knowledge from a broader perspective, expanding the scope of observation to obtain a more comprehensive understanding of students' attitudes towards m-learning.…”
Section: Discussionmentioning
confidence: 99%
“…Our aim is to address the research gap identified in the field of mobile learning (m-learning) focused on economic education at the high school level. Limited studies have been conducted on this topic, with most of the existing research primarily concentrated on higher education [3,[42][43][44]. It is crucial to note that students studying economics will play a pivotal role in the future digital economy.…”
Section: Introductionmentioning
confidence: 99%
“…The results section indicates that research on this topic has primarily focused on university students and students in general in these countries. Ismiyati et al [48] conducted a study to investigate Semarang State University students' intention to use mobile learning as an alternative to in-person learning during the COVID-19 pandemic. Alturki and Aldraiweesh [44] examined students' perceptions of the actual use of mobile learning in higher education during the pandemic, providing a detailed view of their experiences.…”
Section: Analysis Of the Target Population In The Adoption Of Mobile ...mentioning
confidence: 99%